Complement C5-inhibitor rEV576 (coversin) ameliorates in-vivo effects of antiphospholipid antibodies. (October 2014) - Romay-Penabad, Z; Carrera Marin, AL; Willis, R; Weston-Davies, W; Machin, S; Cohen, H; Brasier, A; Gonzalez, EB
Activation of the complement cascade is an important mechanism for antiphospholipid antibody-mediated thrombosis. We examined the effects of rEV576 (coversin), a recombinant protein inhibitor of complement factor 5 activation, on antiphospholipid antibody-mediated tissue factor up-regulation and thrombosis. Groups of C57BL/6J mice ( n  = 5) received either IgG from a patient with antiphospholipid syndrome (APS) or control IgG from normal human serum (NHS). Each of these groups of mice had IgG administration preceded by either rEV576, or phosphate buffer control. For each of the four treatment groups, the size of induced thrombus, tissue factor activity in carotid homogenates, anticardiolipin and anti-β2glycoprotein I (anti-β2GPI) levels were measured 72 h after the first injection. Mice treated with IgG-APS had significantly higher titers of anticardiolipin antibodies and anti-β2GPI at thrombus induction compared with those treated with IgG-NHS. The IgG-APS/phosphate buffer treatment induced significantly larger thrombi and tissue factor activity compared with other groups. Mice treated with IgG-APS/rEV576 had significantly smaller thrombi and reduced tissue factor activity than those treated with IgG-APS/phosphate buffer. The data confirm involvement of complement activation in antiphospholipid antibody-mediated thrombogenesis and suggest that complement inhibition might ameliorate this effect.